Epitope mapping of histo blood group antigens bound to norovirus VLPs using STD NMR experiments reveals fine details of molecular recognition - Fiege, Brigitte; Leuthold, Mila (Glycoconjugate journal, 2017)
Attachment of human noroviruses to histo blood group antigens (HBGAs) is thought to be critical for the infection process. Therefore, we have determined binding epitopes of synthetic type 1 to 6 blood group A- and B-tetrasaccharides binding to GII.4 human Norovirus virus like particles (VLPs) using STD NMR experiments. So far, little information is available from crystal structure analysis studies on the interactions of the reducing-end sugars with the protruding domain (P-domain) of the viral coat protein VP1. Here, we show that the reducing-end sugars make notable contacts with the protein surface. The type of glycosidic linkage, and the identity of the sugar at the reducing end modulate HBGA recognition. Most strikingly, type 2 structures yield only very poor saturation transfer indicating impeded binding. This observation is in accordance with previous mass spectrometry based affinity measurements, and can be understood based on recent crystal structure data of a complex of highly homologous GII.4 P-dimers with H-type 2 trisaccharide where the N-acetyl group of the reducing N-acetyl glucosamine residue points towards a loop comprising amino acids Q390 to H395. We suggest that in our case, binding of type 2 A- and B-tetrasaccharides leads to steric conflicts with this loop. In order to identify factors determining L-Fuc recognition, we also synthesized GII.4 VLPs with point mutations D391A and H395A. Prior studies had suggested that these residues, located in a second shell around the L-Fuc binding site, assist L-Fuc binding. STD NMR experiments with L-Fuc and B-trisaccharide in the presence of wild type and mutant VLPs yield virtually identical binding epitopes suggesting that these two mutations do not significantly alter HBGA recognition. Our study emphasizes that recognition of α−(1→2)-linked L-Fuc residues is a conserved feature of GII.4 noroviruses. However, structural variation of the HBGA core structures clearly modulates molecular recognition depending on the genotype.
Gesehen am 29.08.2019